Social Media Customer Expectations: Brand Engagement in Maintaining Customer Loyalty - L.A. Wibowo; Lisnawati Lisnawati; R. Adzimaturrahmah (JPBM (Jurnal Pendidikan Bisnis dan Manajemen), 2019)
This study aimed to find out the description of the level of brand engagement and customer loyalty on Twitter social media users in Indonesia. The research design of this study was a crosssectional method. This study used a descriptive approach and explanatory survey method. A total of 106 respondents were selected by simple random sampling. A questionnaire was used as a research instrument to collect data from respondents. The analysis technique was a descriptive technique by using frequency distribution. The result showed that brand engagement is in good enough categories, while customer loyalty is in good enough category. The differences in this study located on object research, time research, measuring instruments, literature used, the theory used and the results of the study.